ASEAN 50 regional security cooperation through selected documents - Chua, Daniel; Lim, Eddie Meng Chong (World Scientific Pub., 2012)
With an emphasis on ASEAN as a political-security community, this book puts together selected documents that trace the development of the Association through periods of its formation, the Cold War in Asia, the post-Cold War security environment, its expansion and adaption to the shifting geopolitical dynamics. Through the documents and their accompanying commentaries, 50 Years of ASEAN: A Security Community aims to provide an important resource for researchers of ASEAN and Southeast Asia.